1992
DOI: 10.1093/genetics/131.2.461
|View full text |Cite
|
Sign up to set email alerts
|

Multiplicative vs. arbitrary gene action in heterosis.

Abstract: In this article we investigate multiplicative effects between genes in relation to heterosis. The extensive literature on heterosis due to multiplicative effects between characters is reviewed, as is earlier work on the genetic description of heterosis. A two-locus diallelic model of arbitrary gene action is used to derive linear parameters for two multiplicative models. With multiplicative action between loci, epistatic effects are nonlinear functions of one-locus effects and the mean. With completely multipl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
31
0
1

Year Published

1994
1994
2023
2023

Publication Types

Select...
4
2
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 114 publications
(34 citation statements)
references
References 0 publications
2
31
0
1
Order By: Relevance
“…Epistatic interactions hypothesis emphasizes the favorable alleles in the role of heterosis gain. For any site, the effect can be produced by additive dominant or over-dominance ( Minvielle, 1987 ; Schnell and Cockerham, 1992 ; Frascaroli et al, 2007 ). It should be noted that heterosis in self-pollinated species (e.g., rice) may involve different genetic interactions from heterosis in cross-pollinated species (e.g., maize), so both dominant and epistatic hypotheses may be related ( Garcia et al, 2008 ).…”
Section: Introductionmentioning
confidence: 99%
“…Epistatic interactions hypothesis emphasizes the favorable alleles in the role of heterosis gain. For any site, the effect can be produced by additive dominant or over-dominance ( Minvielle, 1987 ; Schnell and Cockerham, 1992 ; Frascaroli et al, 2007 ). It should be noted that heterosis in self-pollinated species (e.g., rice) may involve different genetic interactions from heterosis in cross-pollinated species (e.g., maize), so both dominant and epistatic hypotheses may be related ( Garcia et al, 2008 ).…”
Section: Introductionmentioning
confidence: 99%
“…Four hypotheses were proposed to explain this; the dominance hypothesis which postulates that the increase in vigor after crossing results from the combination of different dominant alleles contributed by each parent [1]. The heterozygosis hypothesis attributes the increase in vigor to the existence of loci at which the heterozygous state is superior to either homozygotes [2,3]; the pseudo-overdominance hypothesis that attributes the hybrid vigor to the effect of tightly linked genes with favorable dominant alleles in repulsion phase in the parental lines resulting in an apparent overdominance when combined in the hybrid [4]and epistasis hypothesis which explains the increased vigor in the light of the interaction of favorable alleles from two parents at different loci that show additive, dominant and/or overdominant action [5]. Among these hypotheses, heterozygosis gained prominence.…”
Section: Introductionmentioning
confidence: 99%
“…Few previous theoretical studies prove the contribution of epistasis for heterosis. Assuming combined multiplicative action of two additive genes, Minvielle (1987) and Schnell and Cockerham (1992) concluded that dominance is not necessary for heterosis. Additionally, Schnell and Cockerham (1992) showed that the multiplicative action of more genes increase the contribution of dominance, but not epistasis, to heterosis.…”
Section: Introductionmentioning
confidence: 99%
“…Assuming combined multiplicative action of two additive genes, Minvielle (1987) and Schnell and Cockerham (1992) concluded that dominance is not necessary for heterosis. Additionally, Schnell and Cockerham (1992) showed that the multiplicative action of more genes increase the contribution of dominance, but not epistasis, to heterosis. Cockerham and Zeng (1996) and Garcia et al (2008) modelled epistatic linked QTLs.…”
Section: Introductionmentioning
confidence: 99%